The role of artificial intelligence in cosmetic and functional gynecology: Stepping into the third millennium - Giovanni Buzzaccarini; Rebecca Susanna Degliuomini; Andrea Etrusco; Andrea Giannini; Antonio D’Amato; Katerina Gkouvi; Nicolas Berreni; Navneet Magon; Massimo Candiani; Stefano Salvatore (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2024)
Cosmetic and functional gynecology have gained popularity among patients, but the scientific literature in this field, particularly regarding the cosmetic aspect, is lacking. The use of evidence-based medicine is crucial to validate diagnostic tools and treatment protocols. However, the advent of artificial intelligence (AI) offers a promising solution to address this issue. ChatGPT, a sophisticated language model, can revolutionize AI in medicine, enabling accurate diagnosis, personalized treatment plans, and expedited research analysis. Cosmetic and functional gynecology can leverage AI to develop the field and improve evidence gathering. AI can aid in precise and personalized diagnosis, implement standardized assessment tools, simulate treatment outcomes, and assess under-skin anatomy through virtual reality. AI tools can assist clinicians in diagnosing and comparing difficult cases, calculate treatment risks, and contribute to standardization by collecting global evidence and generating guidelines. The use of AI in cosmetic and functional gynecology holds significant potential to advance the field and improve patient outcomes. This novel combination of AI and gynecology represents a groundbreaking development in medicine, emphasizing the importance of appropriate and correct AI usage.